2007
DOI: 10.4269/ajtmh.2007.77.633
|View full text |Cite
|
Sign up to set email alerts
|

Persistent and Untreated Tropical Infectious Diseases Among Sudanese Refugees in the United States

Abstract: A comprehensive medical evaluation to identify persistent and untreated tropical infections among members of the Sudanese group "Lost Boys of Sudan" living in Atlanta, GA, was initiated. Medical examinations and laboratory testing including blood cell counts, liver function tests, stool studies for parasites, hepatitis B serologies, and serologic testing for Schistosoma spp., Strongyloides, and filariae were performed. Preliminary results showed a high prevalence of untreated active schistosomiasis and strongy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The practice of travel medicine with the possibility of imported cases from endemic regions is also of growing concern. Often, because of economic globalization and increased travel and migration (even forced, as occurs with refugees), agents are found in countries different from their source [61]. Because this may cause serious diagnostic difficulties, it is important that physicians from both endemic and non-endemic zones increase their awareness of diseases that have been previously considered to be uncommon in their home countries.…”
Section: Discussionmentioning
confidence: 99%
“…The practice of travel medicine with the possibility of imported cases from endemic regions is also of growing concern. Often, because of economic globalization and increased travel and migration (even forced, as occurs with refugees), agents are found in countries different from their source [61]. Because this may cause serious diagnostic difficulties, it is important that physicians from both endemic and non-endemic zones increase their awareness of diseases that have been previously considered to be uncommon in their home countries.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study from Boston, Massachusetts, asymptomatic refugees with eosinophilia from diverse regions who were evaluated serologically had infection rates of 22% for Schistosoma infection and 39% for Strongyloides infection [17]. A small series suggested that rates of schistosomiasis and strongyloidiasis of 52% and 12%, respectively, among resettled Lost Boys and Girls of Sudan whose specimens were also tested by CDC serological assays [18]. Other studies have also demonstrated high infection rates among nonrefugee immigrant populations, underscoring the global importance of these infections [19].…”
Section: Discussionmentioning
confidence: 99%
“…Beginning in 2000, the immigration of refugees from sub-Saharan Africa markedly increased [89], and today the US settles an estimated 70,000 refugees annually, including 25,000 refugees from Africa [90]. Notable among the refugees are the “Lost Boys and Girls of Sudan,” raised initially in poor Ethiopian refugee camps before relocating to Kenya [89]. Since 2000, almost 4,000 Lost Boys and Girls have been settled in the US.…”
Section: The Distressed Regions Of Poverty In the United Statesmentioning
confidence: 99%